2008
DOI: 10.1007/s00134-007-0941-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with posttraumatic stress symptoms in a prospective cohort of patients after abdominal sepsis: a nomogram

Abstract: Objective To determine to what extent patients who have survived abdominal sepsis suffer from symptoms of posttraumatic stress disorder (PTSD) and depression, and to identify potential risk factors for PTSD symptoms. Design and setting PTSD and depression symptoms were measured using the Impact of Events Scale–Revised (IES-R), the Post-Traumatic Symptom Scale 10 (PTSS-10) and the Beck Depression Inventory II (BDI-II). Patients and participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 53 publications
2
58
1
2
Order By: Relevance
“…Among survivors of many life threatening infectious diseases, psychiatric morbidities were observed (6)(7)(8)(9)12). Similar to CCHF, SARS is an infectious disease that has an acute course, but it is not chronic in process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among survivors of many life threatening infectious diseases, psychiatric morbidities were observed (6)(7)(8)(9)12). Similar to CCHF, SARS is an infectious disease that has an acute course, but it is not chronic in process.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, quarantine duration was correlated with PTSD symptoms (16). In addition to CCHF and SARS, Legionella pneumonia and abdominal sepsis are fatal infectious diseases that have been reported to have psychiatric morbidities (6,12). In a study conducted on legionellosis 17 months after the disease, it was reported that 15z of survivors had PTSD, whereas only one patient sought medical help (6).…”
Section: Discussionmentioning
confidence: 99%
“…Although studies vary as to whether age [2][3][4] increases risk for medically induced PTSD, several other factors are consistently associated with increased risk (Box 1). 2,[4][5][6] Box 1…”
Section: Risk Factorsmentioning
confidence: 99%
“…Elevated and probable posttraumatic stress levels were defined as IES-R total scores above 24 and 32, respectively. 23,24 8. Information-seeking style (32 items): According to the monitoring process model, the way people cope under situations of threat can be classified as either cognitive confrontation ("high monitoring") or cognitive avoidance ("low monitoring").…”
Section: Previously Accessed or Received Information About Geneticsmentioning
confidence: 99%